The role of employee creativity mediation on employee performance among expedition employees in Indonesia - Aldhita Anggreliany Putri; Tantri Yanuar Rahmat Syah (Institute of Computer Science (IOCS), 2023)
This research examines the influence of a high-performance work system, employee innovation, employee performance, entrepreneurial leadership, and organizational justice in courier workers who operate in expedition services in Indonesia during the COVID-19 epidemic. This research selected respondents using purposive sampling. Online surveys gather data. This research included 90 shipping industry employees with two years of experience. The research model is evaluated using SmartPLS and SEM. This study demonstrated that the high-performance work system improves creativity and performance. Employee inventiveness also boosts performance. Hence, employee creativity mediates the performance-high-performance work system link. Secondly, entrepreneurial leadership does not regulate the link between a high-performance work structure, employee inventiveness, and employee performance. This research shows that work happiness does not improve employee performance.